Customized Fiber Post Improves the Bond Strength and Dentinal Penetrability of Resin Cementation System to Root Dentin - Leandrin, T. P. [UNESP]; Fernández, E.; Lima, R. O. [UNESP]; Besegato, J. F. [UNESP]; Escalante-Otárola, W. G.; Kuga, M. C. [UNESP] (Operative Dentistry, 2022)
OBJECTIVE: This study aimed to evaluate the effect of fiber post customization on the bond strength (24 hours and 6 months), resin cement thickness, and dentinal penetrability of Adper Scotchbond Multi-Purpose - RelyX ARC (AS-RA), RelyX U200 (R2), and Scotchbond Universal - RelyX Ultimate (SU-RU) cementation systems to root dentin from the cervical-, middle-, and apical-thirds of the post space. METHODS: One hundred twenty bovine incisors were endodontically treated. After post space preparation, the roots were divided into six groups, according to the luting protocols (AS-RA, R2, SU-RU) and the type of fiber post [noncustomized post (NC) and customized post (C)]. Customization procedures were peformed using a resin composite (Z350 XT). 24 hours (n=60) or 6 months later (n=60), specimens from the cervical-, middle-, and apical-thirds of the post space were submitted to cementation system thickness measurement, bond strength evaluation, and dentinal penetrability analysis with Confocal Laser Scanning Microscopy (CLSM). Failure mode was classified as adhesive, cohesive, or mixed. Data were submitted to ANOVA and Tukey tests (α=0.05). RESULTS: Cementation protocols with customized fiber posts presented the lowest cementation system thickness, regardless of the cementation system or post space-third (p<0.05), and the highest bond strength values (p<0.05), regardless of the third space (p>0.05), for both periods (24 hours or 6 months). The comparison of push-out bond strength values between 24 hours and 6 months showed a reduction in all groups for the cervical-third (p<0.05). For the middle-third, only noncustomized groups showed reduction (p<0.05). For the apical-third, no reduction was observed (p>0.05). CONCLUSIONS: Anatomical customization favored both the bond strength of cements to dentin and the dentinal penetrability, but with lower cementation system thickness, regardless of cement composition and adhesive strategy.